Effects of Crude Saponins Extract of Parkia biglobosa Fruit-Husk on Some Kidney Indices and Serum Electrolytes on Gentamicin-Induced Nephrotoxicity in Male Wistar Rats - Ibrahim, Abubakar; Idi, Jahleel; Abubakar, Zainab; Muhammad Hammari, Abubakar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The effects of crude-saponins extract of Parkia biglobosa fruit husk on gentamicin-induced nephrotoxicity on some kidney function indices in male Wistar rats was studied to determine the nephrocurative potentials of Parkia biglobosa fruit-husk on kidney function. The acute toxicity was conducted on wistar rats fasted overnight providing only water. Each animal was administered with a single oral dose of crude saponins extract up to a dose of 500 mg/kg b.w .Dose up to 500 mg/kg b.w did not cause any mortality or sign of toxicity. Thus the extract is considered safe. Gentamicin administration induced marked nephrotoxicity as evidenced by a significant increase (p<0.05) in serum levels of creatinine, urea, uric acid and BUN levels. A significant increase (p<0.05) in sodium, potassium, bicarbonates and chloride ions levels whereas significant decrease (p<0.05) in calcium ion in the disease control rats. Administration of crude saponins of Parkia biglobosa fruit-husk extract and standard drug (furosemide) was found to improve kidney function indices in comparison with the disease control groups.